Growth and development among infants and preschoolers in rural India: Economic inequities and caregiver protective/promotive factors. (November 2016) - Black, Maureen M.; Fernandez-Rao, Sylvia; Hurley, Kristen M.; Tilton, Nicholas; Balakrishna, Nagalla; Harding, Kimberly B.; Reinhart, Greg; Radhakrishna, Kankipati Vijaya; Nair, Krishnapillai Madhavan
Economic inequities are common in low and middle-income countries (LMIC), and are associated with poor growth and development among young children. The objectives are to examine whether maternal education and home environment quality: 1) protect children by attenuating the association between economic inequities and children's growth and development, or 2) promote children's growth and development, regardless of economic inequities. The sample includes 512 infants and 321 preschoolers in 26 villages in rural India (Project Grow Smart). Data for children: physical growth (weight and length/height measured) and development (Mullen Scales of Early Learning); for mothers/households: economic inequities measured by household assets, education, depressive symptoms, and home environment (HOME Inventory). Data are analyzed with linear mixed models (LMM) for infants and preschoolers separately, adjusted for village/preschool clustering, including asset-by-education/home interactions. Among infants, but not preschoolers, the education/home factor attenuates relations between assets and growth, eliminating differential relations in infant growth between high/low-asset families, suggesting protection. Among infants and preschoolers, the education/home factor is significantly or marginally associated with most child development scales, regardless of economic inequities, suggesting promotion. Strategies to enhance maternal education and home environment quality may protect infants in low-asset families from poor growth, promote development among infants and preschoolers, and prevent early disparities.